Answer:
ask the goggle not 1 you help in thi aap bro your aand me same thing make sorry
Answer:
(- 1, - 2 )
Step-by-step explanation:
Given the 2 equations
x - 3y = 5 → (1)
5x - 2y = - 1 → (2)
Rearrange (1) expressing x in terms of y by adding 3y to both sides
x = 5 + 3y → (3)
Substitute x = 5 + 3y in (2)
5(5 + 3y) - 2y = - 1 ← distribute left side
25 + 15y - 2y = - 1
25 + 13y = - 1 ( subtract 25 from both sides )
13y = - 26 ( divide both sides by 13 )
y = - 2
Substitute y = - 2 in (3) for corresponding value of x
x = 5 + (3 × - 2) = 5 - 6 = - 1
Solution is (- 1, - 2 )
Answer:
Step-by-step explanation:
If Amy received 250 dollars for her bday, but she borrowed before 130,
she will have left:
250-130=120 dollars
27 divided by 40 is equal to 0.675.
Answer:
30
Step-by-step explanation: